Using intermittent pulse oximetry to guide neonatal oxygen therapy in a low-resource context - Walker, Patrick James Berkeley (Arch Dis Child Fetal Neonatal Ed, 2020)
OBJECTIVE: To evaluate the effectiveness of intermittent pulse oximetry in guiding oxygen therapy in neonates in a low-resource setting. DESIGN AND SETTING: Prospective validation study at three hospitals in southwest Nigeria. We performed concealed continuous pulse oximetry on participants to evaluate intermittent SpO(2) monitoring. PATIENTS: We recruited all preterm or low birthweight neonates, and all term neonates who required oxygen therapy, who were admitted to the neonatal ward(s) of the study hospitals during the study period. MAIN OUTCOME MEASURES: Proportion of time preterm/low birthweight neonates on oxygen spent within, above and below the target SpO(2) range of 90%–95%; and the proportion of time term neonates and neonates not on oxygen spent within and below the target range of 90%–100%. RESULTS: Preterm/low birthweight neonates receiving oxygen therapy (group A) spent 15.7% (95% CI 13.3 to 18.9) of time in the target SpO(2) range of 90%–95%. They spent 75.0% (63.6–81.1) of time above 95%, and 2.7% (1.7–5.6) of time below 85%. Term neonates and all neonates not receiving oxygen (group B) spent 97.3% (95% CI 96.4 to 98.6) of time within the target range of 90%–100%, and 0.9% (0.3–1.4) of time below 85%. Guidelines recommended SpO(2) monitoring 3 times per day for all patients, however neonates in groups A and B were monitored an average of 4.7 and 5.3 times per day, respectively. CONCLUSIONS: To better maintain SpO(2) within the target range, preterm/low birthweight neonates on oxygen should have their SpO(2) monitored more frequently than the current 4.7 times per day. In all other neonates, however, monitoring SpO(2) 5.3 times per day appears suitable.